Aplikasi Dan Analisis Statistik Menggunakan Stata Untuk Tsls, Probit, Logit, Dan Tobit - Rahulsep lukas tampubolon; Dani Dani; Yomelin andini; Lala Lala; Mutiara Mutiara; Clinton sinaga; Robin silalahi; Dicky Perwira Ompusunggu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This module discusses the application and statistical analysis using Stata software for Two Stage Least Square (TSLS), Probit, Logit and Tobit models. These models are very useful for overcoming problems of endogeneity, censored data, and binary dependent variables in econometric analysis. This paper aims to provide practical guidance for estimating and interpreting the results of the four models using hypothetical case studies. The demonstration results are discussed critically to provide guidance for readers in applying these models to quantitative research.